Immobilized catalysts for iridium-catalyzed allylicamination: rate enhancement by immobilization - Malakar, Chandi Charan; Helmchen, Günter (Chemistry - a European journal, 2015)
Abstract The first immobilized catalyst for Ir-catalyzed asymmetric allylic aminations is described. The catalyst is a cationic (π-allyl)Ir complex bound by cation exchange to an anionic silica gel support. Preparation of the catalyst is facile, and the supported catalyst displayed considerably enhanced activity compared with the parent homogeneous catalyst. Up to 43?consecutive amination runs were possible in recycling experiments.
Gesehen am 05.06.2020